Excise policy of the tsarist government in the Transcaucasian region in the second half of the XIX – early XX century - Almaz M. Ismailovа (Кавказология)
The article is devoted to the study of the excise policy of Russia in the Transcaucasian region, the degree of its impact on the economic development of the region under study. The purpose of the study is to consider the amount of excise revenues contributed to the Russian treasury from various industries of the Transcaucasian Region and to determine the degree of its impact on the economic development of the region under study. Based on the study, generalization and review of archival materials and pre–revolutionary sources, an attempt is made to identify the features of the excise policy of the tsarist government in the second half of the XIX – early XX century in the studied region. The tasks related to introducing excise duty in the oil, tobacco, drinking and other industries are disclosed, analyzed and summarized. It is concluded that the excise policy was of great importance not only for replenishing the Russian treasury, it also had a significant impact on the development of various industries in the region under study.